A little house Christmas : holiday stories from the Little house books - Wilder, Laura Ingalls, 1867-1957.; Williams, Garth (New York : HarperCollins, 1993)
A collection of stories which describe the experiences of a pioneer girl and her family as they celebrate various Christmases In the Big Woods in Wisconsin, on the prairie in Indian Territory, and On the banks of Plum Creek.
Ages 8-12.
Keywords: Wilder, Laura Ingalls, -- 1867-1957 -- Juvenile fiction; Wilder, Laura Ingalls, -- 1867-1957 -- Fiction; Christmas -- Fiction; Frontier and pioneer life -- Fiction; Family life -- Fiction